Proceedings of the 2nd ACM/IEEE-CS Joint Conference on Digital Libraries 2002
DOI: 10.1145/544220.544231
|View full text |Cite
|
Sign up to set email alerts
|

A graph-based recommender system for digital library

Abstract: Research shows that recommendations comprise a valuable service for users of a digital library [11]. While most existing recommender systems rely either on a content-based approach or a collaborative approach to make recommendations, there is potential to improve recommendation quality by using a combination of both approaches (a hybrid approach). In this paper, we report how we tested the idea of using a graph-based recommender system that naturally combines the content-based and collaborative approaches. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(36 citation statements)
references
References 23 publications
0
32
0
4
Order By: Relevance
“…Coefficient approach could be to use filtering and recommendation mechanisms (Callan & Smeaton, 2003;Huang, Chung, Ong, & Chen, 2002;Torres, McNee, Abel, Konstan, & Riedl, 2004) so as to favor long-tail items over short-tail items for library users, in order to increase the demand, and thus reduce the value of the Gini index. Empirical data collection methods for the identification and classification of libraries and collections in the demand categories have been suggested.…”
Section: Categorymentioning
confidence: 99%
“…Coefficient approach could be to use filtering and recommendation mechanisms (Callan & Smeaton, 2003;Huang, Chung, Ong, & Chen, 2002;Torres, McNee, Abel, Konstan, & Riedl, 2004) so as to favor long-tail items over short-tail items for library users, in order to increase the demand, and thus reduce the value of the Gini index. Empirical data collection methods for the identification and classification of libraries and collections in the demand categories have been suggested.…”
Section: Categorymentioning
confidence: 99%
“…Huang et al (2002) propose a two-layer graph-based recommender system in the context of digital libraries. Books and users represent layer nodes and the edges represent transactions.…”
Section: In Recommender Systemsmentioning
confidence: 99%
“…heterogeneous domains). Huang et al [2002] and Torres et al [2004] found that as more rating data are used as the input for generating recommendations, the accuracy of the recommendations decreased. For example, Torres et al [2004] used reference lists at the end of research papers as users' ratings.…”
Section: Type Of Product (Product Domain) and Preference Heterogeneitymentioning
confidence: 99%
“…First, CF has been used mostly for consumer products, such as CDs, books, and movies [Wingfield 1998] and has only recently been applied to other areas, such as research papers and digital libraries [Huang et al 2002;McNee et al 2002;Torres et al 2004]. In fact, CF is thought to have much potential for improving the information search in digital libraries [Williams 2002].…”
Section: Introductionmentioning
confidence: 99%